Changing the Paradigm in Medial Canthal Reconstruction: The Bridge Principle and the Croissant-Like Keystone Island Perforator Flap as An Alternative for Medium Size Soft Tissue Defects in Internal Canthus Reconstruction. Issue 5 (July 2018) - Kostopoulos, Epameinondas; Agiannidis, Christos; Konofaos, Petros; Kotsakis, Ioannis; Hatzigianni, Panagiota; Georgopoulos, Gerasimos; Papadatou, Zoe; Konstantinidou, Chara; Champsas, Gregorios; Papadopoulos, Othon; Casoli, Vincent
Abstract : Introduction: Medial canthus is a common area of skin cancer prevalence. Defects in this region represent a challenging reconstructive task. The nasal version of keystone perforator island flap (KPIF) has proven its versatility. The aim of the present study was to expand its utilization in the neighbor medial canthus area. A modified croissant-like KPIF (CKPIF) was used resolving inner convexity-related problems. The presence of procerus in the glabella area, bridging a surface from nasalis up to the frontalis, changed the traditional dissecting flap technique. Thus, the authors introduce the bridge principle, which consists of the indirect transfer of the flap to the defect site through a muscular "bridge" (the procerus). The authors report their experience in medial canthal reconstruction combining a modified KPIF with a new dissecting "principle." Methods: From November 2016 to July 2017, a series of patients presenting soft tissue defects of various dimensions in the medial canthus, secondary to tumor extirpation, sustained reconstruction with a CKPIF dissected with the bridge principle. Results: A total of 15 patients were treated with this new technique. Their mean age was 75.3 years. The mean size of the defect was 2.08 cm (length) × 1.5 cm (width). All flaps survived without any sign of venous congestion. A transient epiphora presented in 4 patients (4/15 or 26.6%), which was subsided 2 months later. Conclusion: A new approach following a novel paradigm was introduced to resolve an old problem. Initial outcomes are encouraging. However, longer series are needed to extract definitive and safer conclusion.